Membangun Usaha Mandiri Berbasis Gula Saka “Kolaborasi Akademisi dan Masyarakat Nagari” - Merry Thressia; Rozza Linda; Adrian Fadhli, (PELANTAR PRESS, 2025)
This community service programme was implemented in Nagari Bukik Batabuah in response to the loss of livelihoods following the Mount Merapi disaster. The focus of the activities was on empowering the saka sugar farming group through innovations in food-grade silicone moulds, packaging techniques, digital marketing strategies, business licensing and halal labelling. Saka sugar, a culinary heritage of Minangkabau, has great potential to be developed into a high-value, environmentally friendly household product. The activity was carried out over three days through lectures and workshops, covering the empowerment of saka sugar mould making using safe and flexible food-grade silicone, modern packaging with informative labels, and social media and e-commerce-based marketing strategies. In addition, participants were guided in the process of obtaining business permits and halal certification through the OSS and SIHALAL platforms. The results of the activity showed an increase in the knowledge and skills of partners by ≥ 80–90%, as well as the formation of an Activity Management Unit (UPK) to manage the sugar cane business. This programme is expected to create attractive, safe, and highly competitive sugar cane products in local and international markets, as well as strengthen the cultural and economic identity of the Nagari Bukik Batabuah community